2020
DOI: 10.1002/fsn3.2042
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite‐containing mixture alleviates microbial dysbiosis in dextran sodium sulfate‐induced colitis in mice

Abstract: Inflammatory bowel disease (IBD) is a multifactorial immunomodulatory disorder. In relative nosogenesis, gut microbiota has been the focus of research on IBD. In our previous study, we demonstrated the ameliorating effect of zeolite‐containing mixture (Hydryeast®, HY) on dextran sodium sulfate (DSS)‐induced colitis, through transcriptomics and proteomics. In the present study, we performed further investigation from the perspective of metagenomics using the gut microbiota. C57BL6 mice were provided an AIN‐93G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…The improvement observed in broiler growth may be attributed to several reasons. For example, it is well-known that zeolites possess cation-exchange properties that limit the growth of pathogenic bacteria, thereby creating a healthy environment (Lyu et al, 2021). The results of the immune organ relative weight in Table 2 showed that the addition of different compounds of broiler litter had a significant effect on the relative weight of the liver (P<0.05) but had no significant effect on the spleen, thymus, and bursa Fabricius (P>0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The improvement observed in broiler growth may be attributed to several reasons. For example, it is well-known that zeolites possess cation-exchange properties that limit the growth of pathogenic bacteria, thereby creating a healthy environment (Lyu et al, 2021). The results of the immune organ relative weight in Table 2 showed that the addition of different compounds of broiler litter had a significant effect on the relative weight of the liver (P<0.05) but had no significant effect on the spleen, thymus, and bursa Fabricius (P>0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Proven detoxifying properties of the clinoptilolite materials including PMA-zeolite may also improve the overall health and bone status ( 23 , 24 ). At last, local effects in the intestine as the primary site of PMA-zeolite action, i.e., on the microbiota status, as well as corresponding anti-inflammatory and immunomodulatory effects, are likely to contribute to the bone health as well ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the advance of high‐throughput sequencing, metagenomic sequencing detecting microbial diversity in the whole environmental system has been increasingly mature. Because of huge data volume, ability to detect all microbes including uncultured ones, metagenomic sequencing has been extensively used in fecal and food microbiota analysis (Chen et al., 2020; Lyu et al., 2021; Mao et al., 2015; Xie et al., 2013). For example, Liu et al (Liu et al., 2018) identified Burkholderia and Bacillus as predominant bacterial genus in Gu Tian Qu (71.62%) and Wu Yi Hong Qu (44.73%), respectively, and detected 213 bacterial genus with low abundance via Illumina‐based metagenomic sequencing.…”
Section: Introductionmentioning
confidence: 99%